Предмет: Химия,
автор: VladaVolcova
FeO-Fe2O3-Fe-Fe2(SO4)3- Fe(OH)3-Fe2O3 помогите
Ответы
Автор ответа:
0
4FeO + O2 = 2Fe2O3
Fe2O3 + 3H2 = 2Fe + 3H2O
2Fe + 6H2SO4 = Fe2(SO4)3 + 3SO2 + 6H2O
Fe2(SO4)3 = Fe2O3 + 3SO3
Fe2O3 + 3H2 = 2Fe + 3H2O
2Fe + 6H2SO4 = Fe2(SO4)3 + 3SO2 + 6H2O
Fe2(SO4)3 = Fe2O3 + 3SO3
Похожие вопросы
Предмет: Математика,
автор: elizavetabobynceva9
Предмет: Математика,
автор: izrailovaazman008
Предмет: Литература,
автор: sazi45
Предмет: Математика,
автор: oksanapankrato
Предмет: Математика,
автор: nickx6